Lack of association between screening interval and cancer stage in Lynch syndrome may be accounted for by over-diagnosis; a prospective Lynch syndrome database report - Seppälä, Toni T.; Ahadova, Aysel; Kloor, Matthias (Hereditary cancer in clinical practice, 2019)
Recent epidemiological evidence shows that colorectal cancer (CRC) continues to occur in carriers of pathogenic mismatch repair (path_MMR) variants despite frequent colonoscopy surveillance in expert centres. This observation conflicts with the paradigm that removal of all visible polyps should prevent the vast majority of CRC in path_MMR carriers, provided the screening interval is sufficiently short and colonoscopic practice is optimal.
Gesehen am 04.04.2019